RELEVANCE AND PERSPECTIVES OF EXPERIMENTAL WOUND MODELS IN WOUND HEALING RESEARCH - Lodhi, Santram; Vadnere, Gautam P (Asian Journal of Pharmaceutical and Clinical Research, 2017)
The wound healing process consists of four highly integrated and overlapping phases: Hemostasis, inflammation, proliferation, and tissue remodeling. These phases and their biophysiological functions must occur in the proper sequence, at a specific time and continue for a specific duration at an optimal intensity. There are many factors that can affect wound healing which interferes with one or more phases in this process, thus causing improper or impaired tissue repair. This review was aimed to collect data and made a critical analysis. This will provide concise information regarding different models and parameters used for wound healing study. The data related to different wound models are collected using popular search engines as well as relevant science search engines and database including Google Scholar, Science Direct, and PubMed. A new drug substance can be evaluated for wound healing activity using different in vitro models such as cell culture, chick chorioallantoic membrane model, tube formation on metrigel and capillary growth model. The in vivo wound models such as incision, excision, dead space, burn wound, ischemic wound, and diabetic wound models are frequently used. Each model has specific importance. The limitations and advantages of each are described in this review. Although animal wound repair is an imperfect reflection of human wound healing and its clinical challenges, these models can be fundamental tools for the development of new approaches to rational wound therapy. Â 